Study on Low-Velocity Impact Behavior of Twaron® Fabric Subjected to Double-Impactor Impact from a Numerical Analysis Perspective - Huang, Canyi; Cui, Lina; Qiu, Yiping; Liu, Yajun (Fibres & Textiles in Eastern Europe, 2023)
In the present study, a finite element impact model was developed and analyzed using commercial FEM code ANSYS® and then validated via a drop-weight impact experiment. Moreover, double-impactor impact models were designed and developed with different impact distribution and locations of two impactors to compare impact properties. A total of 18 impact scenarios comprised of asymmetric and symmetric types were performed. The effect of impact location on the impact resistance force and duration time was investigated: the closer the impact point is to the fabric center, the longer the impact duration time. In addition, the effect of impact location on impactor failure deflection was also investigated and it was concluded that regardless of the symmetric or asymmetric impact scenario, the smaller the average distance between the impact location of the two impactors from the fixed boundary, the smaller the overall average failure deflection that occurs. The relevance of impact location and fabric energy absorption capacity was also identified. Furthermore, the effect of impact location on fabric stress distribution and transverse deformation and of the variation of the impact velocity on fabric impact behaviors were investigated. These findings will provide important guidance for engineering soft body armor and composite materials.